Construction of a cognitive aptitude test for Air Force pilot selection - Shahidah Leong Abdullah (Tesis, 2019)
This research has received approval from the Royal Malaysian Air Force (RMAF) and was conducted in three phases. In Phase 1, fourteen critical knowledge, skills and abilities (KSA) were identified through feedback from eight flying instructor. In Phase 2, one hundred and forty-nine multiple-choice items were constructed and administered across two independent groups of respondents. In Phase 3, three sets of 40-items cognitive test were constructed using the blueprint. In conclusion, the research has successfully construsted a cognitive aptitude test that is tailored to the RMAF's requirement.